Issue Information. (Journal of Religious History, 2024)
The Journal of Religious History is a fully refereed international journal that publishes articles and reviews on the role of religion in human history. It explores religion and related subjects, as well as debates on comparative method and theory in religious history. The journal is indexed by various academic databases and is published by the Religious History Association, which promotes the study of religious history in Australia. The association is affiliated with the Australian Historical Association and the International Commission for Comparative Ecclesiastical History. The views and opinions expressed in the journal do not necessarily reflect those of the publisher or editors.